Human Capital Strategy Implementation for Startup Business: Jeeva Works Company - Priyo Hadi Susananto; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Semerdanta Pusaka (Penerbit Kemala Indonesia, 2019)
The needs of modern society especially men are needed barber services to tailored a customer. The right service time and attractive facilities it’s effective to generate customer. This business is a new business model in Indonesia and requires business development. Jeeva works company develops to facilitate customer needs by providing re-model and e-registration application technology over coffeeshop. The combination of barbershop and coffeeshop is developed by Jeeva works company namely Jeeva Barber Coffee. Some of the business development undertaken by analyzing the business environment, developing business strategies, operational strategies, marketing strategies, human capital (HC) strategies, financial strategies and risk management. A good strategy in the field of human capital (HC) affects business development. Jeeva Barber Coffee is a premium barbershop business facilitated by modern application technology so that the role of human capital (HC) is very important to improve the company's operations. The Human Capital (HC) strategy to increase company effectiveness using “The Human Capital Management Frame Works Base on Competency Model” by considering the suitability of culture, habits and characteristics of the cutting & hair care business in Indonesia